PEMBUATAN AKTA PERJANJIAN PENGIKATAN HAK TANGGUNGAN YANG DIBUAT OLEH NOTARIS / PPAT BILA DITINJAU DARI ASPEK HUKUM PERDATA - Markus Palu Weking (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The mortgage bonding agreement as a credit guarantee actually contains a weakness especially when viewed from Article 1320 BW Jo Article 1338 BW, because in the agreement on the bonding of mortgages as collateral there is no consensus in the broad sense of the two sides, but only one-sided. While the creditor has determined its contents in the making of the contract of binding of the mortgage while the applicant in giving the agreement is merely fictitious, because if it does not agree then the credit disbursement will fail. The mortgage bonding agreement as credit guarantee not only contains weaknesses, but also deviates from the principles contained in Article 1320 BW Jo Article 1338 BW. Therefore, the question of the validity of the agreement on binding of mortgages as collateral for credit when viewed from Article 1320 BW Jo Article 1338 BW formally can be said that the agreement is not valid. The issue of the parties' attachment to the credit agreement is that the parties may promise anything, as long as it is not contrary to law and morals, and what is legally agreed is binding on the law. The attachment of the Notary in case of any civil law matters which up to the court of the country may take the position of Witness and may also be a party to the defendant.